Simulations of foams and liquid surfaces - Bradley, Kevin Geoffrey (Trinity College (Dublin, Ireland). School of Physics, 2001)
In this thesis, we combine physics and numerical methods to describe the basic properties of foams and liquid surfaces. In Part I, we provide a brief general introduction to the subject of foam physics, detailing what a foam is and how thin films are liquid surfaces form. We also discuss some uses of foams in industry. In Part II, the structure of foams on a localised, individual bubble or single surface scale, is considered. Crystalline cylindrical foams form an excellent testbed for numerical calculations on the local rheology of a foam. We discuss a new model used in the simulation of these foams and investigate their energies and structural transition points. The model is extended to allow for calculations of wet cylindrical foams. When two identical liquid drops are forced together a thin surface of contact forms between them before they coalesce. We consider a situation when coalescence does not occur and an instability arises as the two drops are forced out of each others way. A model of the two drops is discussed and we investigate any instabilities that arise.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin